Estrutura colonial, padrão de forrageamento e distribuição espacial dos ninhos em uma população de Blepharidatta (formicidae, myrmicinae, blepharidattini) do bioma da caatinga, em Crateús, Ceará, Brasil - Pereira, Janaína Cruz (2013)
Blepharidatta (Myrmicinae, Blepharidattini), an ant genus with a strictly Neotropical distribution, is formed by predatory species whose small colonies nest in soil or leaf-litter. With widely scattered populations, but high nest density in places where they occur, these ants are also noticeable for its close phylogenetic relationship with basal groups of Attini (fungus-growing ants), a fact which places Blepharidatta at the center of discussions and hypotheses on the origin and evolution of symbiosis between ants and fungi. Of the six recognized species, only two are formally described: B. brasiliensis (Amazon Rainforest) and B. conops (Cerrado). A new population (Blepharidatta sp.) was recently found in the Caatinga biome (a savanna-like formation of northeastern Brazil), in the “Reserva Particular do Patrimônio Natural Serra das Almas” (RPPNSA) (Crateús-State of Ceará). The aim of the study was to obtain information about the biology of this population, compare it with that available for other species, particularly B. conops, and discuss the taxonomic identity of this population. The work was carried out in the RPPNSA, in a wooded Caatinga area, where Blepharidatta sp. nests were excavated in order to describe their architecture, as well as to obtain information about the size and composition of the colonies. A detailed analysis of the carcasses ring found around nest openings was used to establish the diet of Blepharidatta sp. whose foraging activity pattern was also investigated by monitoring foragers’ activity during 24 hours periods. The distribution, density and foraging area size of nests were investigated by repeated mapping of nests found in an area of 144 m². The results showed that Blepharidatta sp. and B. conops share some key features of their biology like the basic architecture of their nests built in soil, with wide tunnels and some chambers, the presence of a ring of carcasses around the unique nest opening, monogyny, the presence of phragmotic head in queens and a diet consisting mainly of ants. Accordingly, Blepharidatta sp. and B. conops clearly differ from the Amazon or Atlantic Rainforest species (e.g. B. brasiliensis) that nest in leaf-litter, are polygynous, and whose queens have no phragmotic head. However, significant differences were found between Blepharidatta sp. and B. conops, in particular in the architecture of its nests (more complex and with different types of chambers in Blepharidatta sp.) and the size of the colonies (larger in Blepharidatta sp.). Moreover, Blepharidatta sp. differs from B. conops with respect to queen and brood location in the nests, as well as to the size of the queen frontal disk and the sculpture of the disk cuticle. Two hypotheses are proposed and discussed. In the first, the Blepharidatta population found in the “Reserva Particular do Patrimônio Natural Serra das Almas” would represent a new species, possibly endemic to the Caatinga biome. In the second, this population would represent one extreme in the phenotypic variations observed in all populations forming B. conops species.